A Comedy of Storytelling : Theatricality and Narrative in Apuleius' 'Golden Ass'. - Kirichenko, Alexander (Universitätsverlag Winter, 2012)
HauptbeschreibungCurrent interpretations of Apuleius' 'Golden Ass' cover the entire spectrum from a religious autobiography to an incongruous collection of titillating stories. The goal of this book is to explain the extraordinary polyphony of Apuleius' novel as a product of the 2nd century CE context, in which elite culture (philosophy and sophistic oratory) and popular entertainment not only share the same venues and appeal to the same audiences but also engage in active exchange of subject matter and histrionic techniques. The book argues that Apuleius' narrative represents a mosaic of disc.